2023
DOI: 10.1038/s41598-023-36468-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of blocking immune checkpoints LAG-3 and PD-1 on human invariant Natural Killer T cell function

Abstract: Invariant Natural Killer T (iNKT) cells undergo immune exhaustion during chronic activation caused by cancer and viral infections, such as HIV. Exhaustion is marked by cell dysfunction and increased expression of immune checkpoint proteins programmed cell-death-1 (PD-1) and lymphocyte-activation-gene-3 (LAG-3). We hypothesize that blockade of PD-1 and/or LAG-3 will enhance iNKT cell function. Utilizing peripheral blood mononuclear cells from healthy donors, LAG-3 and PD-1 expression on iNKT cells was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Higher PD-1 expression within the tumors could make CD57 + iNKT cells susceptible to inhibitory signals from PD-L1-expressing tumor cells 77,78 . This reinforces the rationale for combining anti-PD1 blockade with iNKT cell-based immunotherapies 19,77,79,80 .…”
Section: Discussionsupporting
confidence: 68%
“…Higher PD-1 expression within the tumors could make CD57 + iNKT cells susceptible to inhibitory signals from PD-L1-expressing tumor cells 77,78 . This reinforces the rationale for combining anti-PD1 blockade with iNKT cell-based immunotherapies 19,77,79,80 .…”
Section: Discussionsupporting
confidence: 68%
“…15 16 However, chronic stimulation of iNKT cells results in exhaustion that can be overcome by blocking checkpoint molecules such as PD-1. 17 Nelson et al demonstrated recently that iNKT cells showed superior tumor control with PD-1 checkpoint inhibition in a murine model of pancreatic ductal adenocarcinoma. 18 Specificity and cytotoxicity of effector cells can be further increased through the introduction of a chimeric antigen receptor (CAR).…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%